Avaliação da indexação em catálogos de bibliotecas universitárias por meio da recuperação da informação - Piovezan, Luciana Beatriz [UNESP] (2015)
Whereas the subject indexing process as a method of knowledge organization and representation and the subject indexing policy, as a philosophy regulating the performance of indexing by providing guidelines that aim to make the information system most efficient, this dissertation has as its theme the evaluation of subject indexing in university libraries' catalogs. Given the imperative of an agenda that puts into practice and in the routine of information units the performing of evaluation studies of the process and product of subject indexing, we had as research problem the need to investigate such issues, specifically in the context of academic libraries, given the necessary avant garde characteristic of these organizations on issues of information. Thereby, the proposition was to perform comparative evaluation of subject indexing performed in catalogs of systems of academic libraries using the method of extrinsic evaluation through consistency. The aim was to contribute to studies concerning the practice of subject indexing and subject indexing evaluation in the context of knowledge organization on Information Science and the specific goals were to perform theoretical and methodological study on subject indexing and subject indexing evaluation in the field of knowledge organization and placing them in the context of academic libraries; to apply comparative study evaluating the subject indexing performed in two catalogs of systems of academic libraries and analyze the consistency of indexing as indicators of the quality of subject indexing in catalogs of systems of academic libraries. In order to do so, carried out a review of national and international literature on these topics as well as about the current context of academic libraries and applied comparative study of the subject indexing performed on two catalogs, using the method of extrinsic evaluation through consistency. The results found a strict consistency index of 24,88% and...